A Practical Access to Highly Enantiomerically Pure Flavanones by Catalytic Asymmetric Transfer Hydrogenation. Issue 44 (11th September 2013) - Lemke, Marie‐Kristin; Schwab, Pia; Fischer, Petra; Tischer, Sandra; Witt, Morris; Noehringer, Laurence; Rogachev, Victor; Jäger, Anne; Kataeva, Olga; Fröhlich, Roland; Metz, Peter
<x xml:space="preserve">Abstract</x> A surprisingly selective, non‐enzymatic kinetic resolution of readily available, racemic β‐chiral ketones enabled the title process, which was applied to a rapid synthesis of several bioactive flavanones in virtually enantiopure form (see scheme; MOM=methoxymethyl, Ts=p‐toluenesulfonyl).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>